Non-Catalytic and γ-Al2O3 Catalyst-based Degradation of Glycerol by Sonication Method - Ruslan Kalla; Sumarno Sumarno; Mahfud Mahfud (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
This research aims to study the effect of the addition of the catalyst γ-Al2O3 on the degradation of glyc-erol with using sonication method. This degradation reaction performed with the aid of a catalyst γ-Al2O3 or without a catalyst. Reactants were prepared from glycerol-water mixture with a mass ratio of 1:8. Experiment was carried out in a batch reactor at atmospheric pressure, temperature range be-tween 30-70 °C for 10-90 min. The products, which were degraded from glycerol, were analyzed by gas chromatography (GC). The results showed that the ultrasonic wave radiation could degrade glycerol. The glycerol conversion was 2.92%-59.95% without employing catalyst, while the conversion of glycerol increased with adding γ-Al2O3.catalyst. It was found that methanol, allyl alcohol and acrolein were deg-radation products. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).